Hydrogen production from glycerol using copper and nickel loaded zeolite based catalyst - Abdul Halim Yun, Hafizah (2013)
The increasing of the growth rate for vehicles leads to the high production of biodiesel and gives a large amount of glycerol as the by-product via transesterification reaction. Moreover, the limited of the world demand for glycerol makes the glycerol as a waste and abundant substance. For that reason, glycerol conversion into valuable chemical such as hydrogen fuel production is essential since conventional source of hydrogen production is mainly from fossil. Commonly, the metal catalyst which been used for hydrogen production via steam reforming is costly that give worrisome to the industries. Therefore, in this study, copper (Cu) and nickel (Ni) metal loaded on HZSM-5 zeolite catalyst is used for hydrogen production from glycerol via steam reforming. The study is focusing in analyzed the performance of Cu and Ni metal loaded on HZSM-5 and investigates the optimum conditions for hydrogen production which include reaction temperature, glycerol feed concentration or water/glycerol molar ratio (WGMR) and feed flow rate. The hydrogen production through steam reforming was carried out using a fixed bed type reactor while the range of studied parameters for reaction temperature (350-750oC), glycerol feed concentration (3:1-11:1 of WGMR) and feed flow rate (0.25-1.25mL/min) were performed. The catalyst performance for hydrogen production was observed by different weight percentage of Cu (0.5-10%) and Ni (0.5-10%) loaded on HZSM-5 catalyst. It was found that 5wt% of Cu with 10wt% of Ni to be the best catalyst to produce higher hydrogen yield. By using statistical design, the optimum of hydrogen yield (3.98 of mol H2/mol C3H8O3 converted) was achieved at temperature 639oC, 8:1 of WGMR and flow rate of 0.65mL/min.